Incidence and Factors Associated with Graft-Versus-Host Disease in the First Year After Allogeneic Peripheral Blood Stem Cell Transplantation - Ulrike Heider; Julio Solano-Vega; Y. Gisella Sandoval-Vargas; Cándida Díaz-Brochero (Journal of Immunotherapy and Precision Oncology)
Introduction The use of allogeneic peripheral blood stem cell transplantation (allo-SCT) has increased in Latin America in recent years. In the absence of an matched-related donor (MRD), haploidentical transplantation has emerged as a potentially curative option with increasing availability in the region. Graft-versus-host disease (GVHD) is an important complication with variable incidence rates depending on the type of transplant. The aim of this study was to compare the incidence of acute and chronic GVHD between haploidentical and identical allo-SCT recipients and to analyze factors associated with the development of GVHD during the first year after transplantation. Methods Our retrospective cohort study included adult patients with malignant and nonmalignant hematologic pathologies who received allo-SCT between 2014 and 2022 at a transplant center in Bogota, Colombia. Uni- and multivariate analyses were performed to determine factors associated with the development of GVHD. Results A total of 152 patients were analyzed, including 108 (71%) transplants from an MRD and 44 (28.9%) transplants from a haploidentical donor. The median age was 45 years. The most common indications for transplantation were acute myeloid leukemia (37.5%) and acute lymphoblastic leukemia (36.2%). The incidence of acute GVHD was greater in the haploidentical transplant group (63.0%) than in the MRD group (36.6%) (p < 0.05). There was no significant difference in the incidence of chronic GVHD between the two groups, with 18% and 33% in transplants from haploidentical donors and MRD, respectively (p = 0.09). The factors associated with the development of acute GVHD were relapse (odds ratio [OR] 0.41; 95% CI, 0.13–1.16), female sex (OR 2.34; 95% CI, 0.93–6.1), and age older than 50 years (OR 2.1; 95% CI, 0.81–5.71). The factors associated with the development of chronic GVHD were haploidentical donor status (OR 0.22; 95% CI, 0.05–0.75) and relapse (OR 0.16; 95% CI, 0.04–0.56). Conclusions Our study revealed a higher rate of acute GVHD in transplant recipients from a haploidentical donor than in those from MRD, whereas no differences were found for chronic GVHD between the two groups. Sex, age, relapse, and type of transplant were identified as factors associated with the prevalence of GVHD.